Evaluation of a Brief Format of the Triple P-Positive Parenting Program: A Pilot Study With Indonesian Parents Residing in Australia. Issue 2 (21st May 2014) - Sumargi, Agnes; Sofronoff, Kate; Morawska, Alina
<x content-type="archive" xml:space="preserve">Abstract</x> Dissemination of evidence-based parenting programs in developing countries is warranted, but prior to dissemination, the cultural appropriateness of programs needs to be assessed. This study provides an evaluation of the level of acceptability among Indonesian parents and the efficacy of a brief parenting program, the Triple P-Positive Parenting seminar. Thirty Indonesian parents of children aged 2–12 years old residing in Australia participated in the study. A 90-minute Triple P seminar with minimal changes in the format was delivered to parents in Indonesian. Parents reported a high level of acceptability and satisfaction with the program content. The efficacy of the program was also explored. Parents reported less frequent use of dysfunctional parenting practices, particularly permissive parenting style, and reduction in the intensity of child emotional and behavioural problems 3 weeks after the seminar. The effect was maintained at 3-month follow up. The results suggest that the Triple P seminar is acceptable and useful for Indonesian parents. Substantial changes in the content of the parenting program may not be necessary. Translated materials, culturally relevant examples and opportunity for questions appeared sufficient for parents. Future studies are required, including randomised controlled trials and larger sample sizes.